INNOVATIONS IN THE AGRICULTURAL BUSINESS: PROBLEMS AND PROSPECTS IN UKRAINE - Tetiana Mulyk; Yaroslavna Mulyk (International Journal of Innovative Technologies in Economy, 2020)
The main purpose of the research is to determine the role of innovation of agrarian enterprises for their effective management, as well as analysis of the internal and external environment of innovation activity of agrarian enterprises, their threats and opportunities with the help of SWOT-analysis. The systematization of literary sources and approaches to innovative activity of agrarian enterprises made it possible to generalize that the fundamental questions related to the interpretation of the essence of innovations, innovation activity and innovative processes of enterprises, with the specifics of their manifestation in agrarian enterprises, were investigated by domestic and foreign scientists as well as regulated by normative- legal acts. The urgency of solving this scientific problem lies in the fact that the determining factor of the efficiency of economic activity of the enterprise is their innovative development, which is based on the introduction and implementation of innovations, which determine the improvement of its activities, affect the strengthening of its market positions and produce suitable conditions for its development. One of the promising areas for innovations is the agrarian sector. Introduction of innovations in practice in all spheres of agrarian enterprises contributes to: the increase of labor productivity, decrease of expenses and cost of production, saving of various kinds of resources, increase of volumes and improvement of efficiency of agrarian production. The article analyzes the main directions of IT innovations in agrarian business, innovative solutions (products) and opportunities. It is determined, that any agrarian enterprise has its own peculiarities and specificity and requires individual innovative solutions. The management of the company often can easily identify, what is needed to increase the efficiency. And sometimes the services of analysts and IT consultants, who are professionals of their business, and can unmistakably determine the individual needs and decisions, can be useful. The peculiarities of formation and development of innovation process in agriculture were analyzed. A SWOT analysis of innovative activity of agrarian enterprises was conducted, which allowed to identify their strengths (weaknesses) sides, opportunities and threats. The results of the research can be useful for scientists, specialists and heads of agrarian enterprises, teachers of higher educational establishments, postgraduates, students and all those, who are interested in problems of development and efficiency of innovation activity.